Improvement of Infection Prevention and Control Practices Using Quality Improvement Approach in Two Model Hospitals in Kenya. (October 2020) - Kihungi, Loyce; Ndinda, Mary; Dolan, Samantha; Wesangula, Evelyn; Ndegwa, Linus; Owiso, George; Lynch, John; Frisbie, Lauren; Rabinowitz, Peter
Abstract : Background: Little is known about how best to implement infection prevention and control programs in low-resource settings. The quality improvement approach using plan-do-study-act (PDSA) cycles provides a framework for data-driven infection prevention and control implementation. We used quality improvement techniques and training to improve infection prevention and control practices in 2 model hospitals in Kenya. Methods: The 2 hospitals were chosen by the Kenya Ministry of Health for capacity building on infection prevention and control. At each site, the project team (the University of Washington International Training for Education and Training in Health, Ministry of Health, and Centers for Disease Control) conducted infection prevention and control training to infection prevention and control committee members. Infection prevention and control quality improvement activities were introduced in a staggered manner, focusing on hand hygiene and waste management practices. For hand hygiene, the project team's technical assistance focused on facility hand hygiene infrastructure, hand hygiene practice adherence, hand hygiene supply quantification, and monitoring and evaluation using WHO hand hygiene audit tools. Waste management technical assistance focused on availability of policy, guidelines, equipment and supplies, waste segregation, waste quantification, and monitoring and evaluation using a data collection tool customized based on previously published tools. Regular interactive video conference sessions between the project team and the sites that included didactic sessions and sharing of data provided ongoing mentorship and feedback on quality improvement implementation, data interpretation, and data use. Results: Hand hygiene data collection began in April 2018. In hospital A, hand hygiene compliance increased from a baseline of 3% to 51% over 9 months. In Hospital B, hand hygiene compliance rates increased from 23% at baseline to 44% after 9 months. Waste management data collection began in November 2018. At hospital A, waste segregation compliance scores increased from 73% at baseline to 80% over 6 months, whereas hospital B, waste segregation compliance went from 44% to 80% over 6 months. Conclusions: A quality improvement approach appears to be a feasible means of infection prevention and control program strengthening in low resource settings. Funding: None Disclosures: None